Yoga as a Therapeutic Intervention in the Management of Dysfunctional Uterine Bleeding: A Controlled Pilot Study - Snehal Pankaj Nalgirkar; Suhas Ashok Vinchurkar; Apar Avinash Saoji; Sriloy Mohanty (Wolters Kluwer Medknow Publications, 2018)
Background: Dysfunctional uterine bleeding (DUB) is one of the most common gynecological disorders encountered in women during the reproductive age. Yoga therapy has shown promising benefits in several gynecological disorders. Methods: Thirty women between the ages of 20 and 40 years with primary DUB were randomly assigned to a yoga (n = 15) and a waitlist control group (n = 15). Participants in the yoga group received a 3-month yoga module and were assessed for hemoglobin values, endometrial thickness (ET), pictorial blood loss assessment chart (PBAC), State-Trait Anxiety Inventory, perceived stress scale, and Pittsburgh Sleep Quality Index (PSQI) before and after a 3-month follow-up period. Results: At the end of 3 months of intervention, the yoga group, unlike the control group, reported a significant reduction in the anxiety scores (P < 0.05) and perceived stress (P < 0.05). The PSQI scores indicated a reduction in sleep disturbances (P < 0.001) and the need for sleep medications (P < 0.01) and higher global scores (P < 0.001). However, there were no changes in PBAC and ET in both the groups. Conclusion: The results indicate that yoga therapy positively impacts the outcome of DUB by reducing the perceived stress and state anxiety and improving the quality of sleep. This warrants larger clinical trials to validate the findings of this pilot study.